ESTRUS INDUCTION AND FERTILITY RESPONSE IN POSTPARTUM ANOESTRUS SURTI BUFFALOES TREATED WITH NORGESTOMET EAR IMPLANTS ALONE AND IN COMBINATION WITH PMSG - PARMAR, S C; KHASATIYA, C T; PATEL, M D; CHAUDHARY, J K; PATEL, R V (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on eighteen postpartum anoestrus (> 45 days postpartum) Surti buffaloes, divided into three equal groups (6 in each) to evaluate the efficacy of Norgestomet ear implant/Crester alone (Gr-I) and in combination with PMSG (Gr-11). The buffaloes in Group-I and Group-II were implanted with Crestar ear implant for 9 days with 2 ml i/m injection of Crestar solution (estradiol valerate) on the day of implant insertion. In Group-II, additionally 500 IU PMSG was given i/m on the day of implant removal. The buffaloes in Group-Ill served as untreated anoestrus controls and were given 5 ml normal saline i/m as a placebo treatment on days 0 and 9. The estrus was induced in all buffaloes in Gr-I and II with mean estrus induction intervals of 2.56 ± 0.34 and 2.40 ± 0.29 days, respectively. These intervals were significantly (P<0.01) shorter as compared to control Gr-Ill (30.33 ± 0.95 days). The duration of estrus differed significantly (P<0.01) being longest (25.50 ± 0. 76 hrs) in Gr-II followed by Gr-I (22.17 ± 0.65 hrs) and the least in control Gr-Ill (18.67 ± 0.77 hrs). The intensity of estrus differed significantly (P<0.05) among these three groups. The conception rate at induced estrus was highest (66.67 %) in Gr-II followed by Gr-I (33.33 %) and Gr-Ill (16.67%). The mean of number of services per conception did not differ significantly among the treatment and control groups. The service periods of the anoestrus buffaloes under Gr-I and II were significantly (P<0.01) shorter than in control Gr-Ill. lt could be concluded that Norgestomet ear implant alone and in combination with PMSG can be successfully used to induce fertile estrus in the postpartum anoestrus Surti buffaloes.